PENGARUH E-RESOURCES TERHADAP PRESTASI AKADEMIK YANG DIMEDIASI OLEH PERCEIVED USEFULNESS - Anton Risparyanto; R. Edi Fitriyanto (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
Academic achievement directly or indirectly (through perceived usefulness mediation). influenced by the availability of electronic information sources (e-resources). This study aims to determine the significant value of probability: (1) The effect of electronic information sources (e-resources) on perceived usefulness: (2) The effect of perceived usefulness on academic achievement and (3) The direct or indirect influence of electronic information sources (e-resources) ) library on academic achievement. Furthermore, the results of this study are expected to be used as a recommendation material for conceptual formulation in improving student academic achievement through electronic information sources (e-resources) and perceived usefulness. This quantitative research consists of three variables including: electronic information sources (e-resources) as the independent variable, academic achievement as the dependent variable and functioning as an intervening variable, namely perceived usefulness. 100 samples of data were taken by probability from a population of 134. The data analysis used included the classic assumption test, the t hypothesis test and the Determinant (R2) test through path analysis. The results of the study show that: (1) Electronic information sources (e-resources) have a significant effect on perceived usefulness) as indicated by the probability p-value of 0.000 with a t-value of 6,757 which is less than 0.05 (p-value = 0.000 < 0.05); (2) Perceived usefulness has a significant effect on academic achievement with a t-value of 4,579 and a probability of less than 0.05 (p-value = 0.000 <0.05); (3) So directly electronic information sources (e-resources) have a significant effect on academic achievement by 24.2%. with a p-value probability of 0.000 with a t-count value of 6,757 less than 0.05 (p-value = 0.000 <0.05) Likewise, indirectly (through perceived usefulness mediation) a significant effect on academic achievement is shown with a t value of 3.78294426 with a std error of 0.0812436 and a significant probability value of 0.00015498 p-value of 30.734%.